Accuracy of Coracoid Bone Graft Placement: Open versus Arthroscopic Latarjet - Russo, Adriano; Grasso, Andrea; Arrighi, Annalisa; Pistorio, Angela; Molfetta, Luigi (Joints, 2017)
Purpose The aim of this study was to compare the accuracy of the coracoid bone graft placement with the open Latarjet-Patte and arthroscopic Latarjet (arthro-Latarjet) procedures in the treatment of anterior instability of the shoulder.Methods Forty-six patients affected by anterior shoulder instability were divided into two groups. In group A (n = 25), patients were operated by arthroscopic Latarjet (arthro-Latarjet) procedure and in group B (n = 21), patients were operated by open Latarjet-Patte procedure. Instrumental investigation was based on three-dimensional computed tomography (3D-CT) at a minimum 1-year follow-up. Graft placement and integration, divergence and posterior protrusion of the screws, and glenohumeral osteoarthritis were considered as outcomes. Statistical analysis was performed with chi-square or Fisher's exact test. Significance was set at p < 0.05.Results Positioning of the coracoid graft proved to be optimal in 76% (19/25) of patients of group A and in 100% (21/21) of patients of group B (Fisher's exact test, p = 0.025). Screw placement with respect to the glenoid surface showed a posterior divergence in 44% (11/25) of patients in group A and in 24% (5/21) of patients in group B (p = 0.15). Posterior protrusion of screw was observed in 76% (19/25) of patients in group A and 71.4% (15/21) of patients in group B (p = 0.73). Graft integration was present in 76% (19/25) of patients in group A and 85.7% (18/21) of patients in group B (Fisher's exact test, p = 0.48). Mild signs of glenohumeral osteoarthritis were observed in 12% (3/25) of patients in group A and 28.6% (6/21) of patients in group B (Fisher's exact test, p = 0.26).Conclusion Patients operated with open Latarjet-Patte procedure showed better results than those of the arthro-Latarjet group in reference to the positioning of the graft on the coronal plane (p = 0.025). No significant differences between the groups were observed for graft integration, divergence of the screws, posterior protrusion of the screws, and osteoarthritis.Level of Evidence Level II, nonrandomized prospective comparative study.
Keywords: arthroscopic; coracoid graft; instability; Latarjet-Patte; shoulder; computed tomography